Mapping potential motorised sightseeing recreation supply across broad privately-owned landscapes of the Southern United States. (4th July 2018) - Merry, Krista; Bettinger, Pete; Siry, Jacek; Bowker, J. M.; Weaver, Steven; Ucar, Zennure
Abstract: The recreational opportunities available across landscapes of the Southern United States can be broad and diverse, and collectively are considered a subset of cultural ecosystem services. In describing the settings of recreational opportunities, a number of methods have been proposed that are based in part on geographic information and that can be facilitated by geographical analyses. Presented here are two expedient and cost-effective methods for assessing the recreation supply potential of large, heavily-roaded areas that are situated mainly with privately-owned land in the Southern United States. One land classification process uses fine-scale aerial imagery and other geospatial data in a process that results in three recreational opportunity setting zones with a focus on motorised sightseeing: foreground, background, and remote areas. Within these zones, land cover was derived and aggregated into three major land cover classes, including forest, agriculture, and bare ground classes. Further, a second process uses fuzzy classification methods, and through this highly suitable recreation settings were identified. Each recreational opportunity zone is further subdivided by public- and privately-owned land. We feel these types of recreation setting models can allow managers and planners to gain an understanding of the passive recreation potential of heavily-roaded privately-owned landscapes typical of the Southern United States.